Nellie Sue, happy camper - Janni, Rebecca; Avril, Lynne (Penguin Young Readers, an imprint of Penguin Group (USA) Inc. New York, New York, 2013)
Like all cowgirls, Nellie Sue loves to go camping so after she and her friend Anna practice indoors, Daddy helps them pitch their tent in the wilderness of the back yard